System error : war is a force that gives us meaning - Exhibition. System error : war is a force that gives us meaning. Siena. Palazzo delle Papesse Centro Arte Contemporanea Siena. 2007-02-03. 2007-05-06; Anastas, Ayreen; Ashford, Doug; Durham, Jimmie; Fisher, Jean; Fusco, Coco; Fusi, Lorenzo; Gabri, Rene; McAllester, Matthew; Mohaiemen, Naeem; Neufeld, Josh; Rakowitz, Michael; et al. (Siena : Palazzo delle Papesse Centro Arte Contemporanea Siena Silvana Editoriale Cinisello Balsamo (Milano), 2007)
Alfred, Brian ; Alkadhi, Rheim ; Anderson, Dawolu Jabari ; Aranda, Julieta ; Bhattacharjee, Shishir ; Bridgland, Sarah ; Bryans, Matt ; Carter, Kevin ; Dedomenici, Richard ; Dieker, Birgit ; Gal, Meir ; Gmelin, Felix ; Haddock, Jon ; Haque, Usman ; Jaar, Alfredo ; Jacir, Emily ; Kalinowska, Agnieszka ; Marker, Chris ; Miller a.k.a. DJ Spooky that subliminal kid, Paul D. ; Motta, Carlos ; Moukarbel, Chris ; Naka, Chris ; Negativland ; Ngamchalee, Chaleerat ; Nicholson, Tom ; Niksic, Damir ; Palumbo, Stefano ; Peress, Gilles ; Pickering, Sarah ; Prieto, Wilfredo ; Raad, Walid ; Sacco, Joe ; Salloum, Jackie ; El-Sherbini, Yara ; Simeti, Francesco ; Speculative Archive ; Suh, Do-Ho ; The Critical Voice ; Vidal, Alejandro ; Woods, Lebbeus
CD in speciale kast
biog. p. 332-335
Engels
Italiaans
boek